2013
DOI: 10.1002/jso.23365
|View full text |Cite
|
Sign up to set email alerts
|

Trends in post-mastectomy reconstruction: A SEER database analysis

Abstract: Background and Objectives This study was performed to investigate recent trends and factors associated with immediate breast reconstruction (IBR) using a large population-based registry. We hypothesized that rates of IBR have increased since passage of the Women’s Health and Cancer Rights Act of 1998. Methods The SEER (Surveillance, Epidemiology and End Results) database was used to evaluate Stage I–III breast cancer (BC) patients who underwent total mastectomy from 1998–2008. Univariate and multivariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 34 publications
8
50
0
5
Order By: Relevance
“…As recognition of the genetic component of familial breast cancer grows and genetic testing has become more available, rates of bilateral prophylactic mastectomy and contralateral prophylactic mastectomy have increased in high‐risk patients9 10. Furthermore, a trend has also been reported for women who are eligible for breast‐conserving surgery to opt for mastectomy3 11, 12, 13 and contralateral prophylactic mastectomy in the unaffected breast13, 14, 15, 16, 17, despite a lack of evidence of a survival advantage for this approach in the absence of a known genetic mutation.…”
Section: Introductionmentioning
confidence: 99%
“…As recognition of the genetic component of familial breast cancer grows and genetic testing has become more available, rates of bilateral prophylactic mastectomy and contralateral prophylactic mastectomy have increased in high‐risk patients9 10. Furthermore, a trend has also been reported for women who are eligible for breast‐conserving surgery to opt for mastectomy3 11, 12, 13 and contralateral prophylactic mastectomy in the unaffected breast13, 14, 15, 16, 17, despite a lack of evidence of a survival advantage for this approach in the absence of a known genetic mutation.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Immediate breast reconstruction has been shown to improve body image, psychological well-being, and overall quality of life in breast cancer patients. 1418 Numerous studies have demonstrated the oncologic safety of immediate breast reconstruction for patients with invasive breast cancer, 1921 and some argue that immediate compared with delayed breast reconstruction offers superior aesthetic and psychosocial benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Dans une récente méta-analyse, Gieni et al [6] rapportent l'absence de sur-risque observée dans les études rétrospectives observationnelles (793 patientes opérées par mastectomie avec RMI et comparées à 2917 patientes sans RMI), ainsi que dans les études rétrospectives avec appariements sur les paramètres histo-pronostiques des cancers (358 patientes avec RMI appariées au même nombre de patientes sans RMI). La sécurité carcinologique de la RMI étant démontrée, une augmentation croissante du nombre de procédure de RMI est observée avec l'année de prise en charge du cancer [2,4]. De même, concernant les délais à l'initiation des traitements adjuvants, la RMI est associée avec une augmentation modérée, cliniquement non significative, avec un délai supplémentaire moyen de 2 semaines environ en fonction des séries [16,17].…”
Section: Discussionunclassified
“…Le taux de reconstruction mammaire immédiate (RMI) est en augmentation régulière dans la plupart des pays développés [1][2][3][4], en raison de la preuve de son bénéfice sur le bien-être des patientes opérées par mastectomie pour cancer du sein et de son innocuité carcinologique [5,6]. Parmi les techniques de reconstruction, le lambeau de grand dorsal sans prothèse (LGDSP) est une technique fiable qui donne d'excellents résultats en reconstruction mammaire.…”
Section: Introductionunclassified